Manajemen Sarana Prasarana Pendidikan di MTs Negeri 7 Bantul Yogyakarta - Adiarti, Winda; Setiawan, Farid; Qatrunnada, Nisrina; Alfiani, Avni (ALSYS, 2022)
This research was conducted at MTS Negeri 7 Bantul with the aim of finding out how the management of facilities and infrastructure that had been implemented at MTS Negeri 7 Bantul was running well and correctly, and what effect the existence of these facilities had on student achievement. With the qualitative method, the authors make observations directly to the school, collect data from existing information and then conduct analysis. The existing infrastructure at MTS Negeri 7 Bantul has been running well, with it being able to support student achievement. One of them is the school implements a self-development program so that students can express their talents according to the potential they have in each individual. With this program, students have received several achievements.